EVALUATION OF THE DEVELOPED HARDWIRED MECHATRONIC TRAINERS AS AN EDUCATIONAL DEVICE - Pepito, Joseph C; Montecillo, Romeo P; Cordero, Lelanie S; Del Fierro, Esperanza M; Ocampo, Christine Omela V; Siglos, Kenneth A (Journal of Agriculture and Technology Management, 2022)
Mechatronics is a multidisciplinary discipline that refers to the skill sets required in the current, advanced computerized manufacturing industry incorporating electronics and mechanical engineering, computer systems, and advanced controls systems to products and processes. Mechatronics is a crucial foundation for the projected growth in manufacturing and automation. Cebu Technological University (CTU) - Main Campus offers a mechatronics program that aims to address the need for the future employment demand in industrial automation. The study aimed to assess the newly-developed hardwired mechatronic trainer- equipment needed for instruction to strengthen the quality of education. It employed a descriptive-normative survey method using a questionnaire duly evaluated by experts, including industry representatives, peers, and friends who have interests and experience in dealing with industrial automation. Results suggested that the program professors met the educational and industry experience qualifications specializing in mechatronics or automation technology. Also, it showed that there is a significant difference (P=.000) between the perception of the students and professors on the trainer. The teachers and students may have different views in evaluating the innovation of the mechatronic trainers. However, they share the same hope: to have a well-functioning mechatronic trainer. Therefore, the development of an innovative mechatronics trainer is very effective in delivering relevant skills in mechatronics from the students’ perspective, requiring both professors and students to fully utilize all laboratory facilities until they become familiar and used to have a complete understanding of the required knowledge and skills in mechatronics.